(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this work some substituted triazole, and pyrrolopyrazine derivatives were synthesized. Triazole were synthesized by using and treating acetaldehyde with pyrazinamide in presence of hydrazine hydrate and total 6 derivatives (A1-A6) were prepared by using Ar-NH2. Pyrrolopyrazine were synthesized by using and treating pyrazinamide with substituted acetaldehyde to obtain corresponding imines, on cyclization by polyphosphoric acid, pyrrolopyrazine derivatives were prepared by mannich reaction(B1-B9). All the synthesized compounds were characterized by 1H-NMR, IR and Elemental Analysis. All the compounds were evaluated for antibacterial (E. coli and S.aureus) and were measured in terms of zone of inhibition and compared with the standard drug ciprofloxacin for antibacterial activity. All the compounds were evaluated for antitubercular activity (M. tuberculli) at 25µg/ml, 50µg/ml and 100µg/ml concentrations. And their results were compared with the standard drug streptomycin from them three compounds have shown promising activity.